1970
DOI: 10.5812/ircmj.16769
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking Behavior and the Related Factors Among the Students of Mashhad University of Medical Sciences in Iran

Abstract: Background:Tobacco consumption is the second major cause of death and the fourth most common risk factor for diseases, worldwide. Epidemiologic studies have traced the use of alcohol, tobacco, and illicit substances among medical students and physicians.Objectives:The current study aimed to investigate the prevalence of cigarette smoking and the related factors among the students of medical sciences in Mashhad University of Medical Sciences, Mashhad, Iran.Patients and Methods:This cross-sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…Surprisingly, 430 (87%) of the smoker group had no family history of a first‐degree relatives smoking, while the nonsmoker group had 100 (20%) of family members smoking ( P = .439) which made a history of a first‐degree relative a noninfluential factor in persuasion to smoking. Our results came in agreement with a number of studies that reported friends to be the most influencing factor associated with the persuasion for starting smoking 28‐30 …”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, 430 (87%) of the smoker group had no family history of a first‐degree relatives smoking, while the nonsmoker group had 100 (20%) of family members smoking ( P = .439) which made a history of a first‐degree relative a noninfluential factor in persuasion to smoking. Our results came in agreement with a number of studies that reported friends to be the most influencing factor associated with the persuasion for starting smoking 28‐30 …”
Section: Discussionsupporting
confidence: 93%
“…25 An increasing trend of tobacco smoking is anticipated to occur among university students and this could be related to perceived alleviation of stress, life problems, peer pressure, social acceptance, class history of smoking, lower educational level of parents, and the desire to attain higher societal class. [26][27][28] Smoking among students in Bangladesh has been poorly investigated and our initial hypothesis was that it is possible that university students may be lacking knowledge on the link between smoking and adverse health effects. The aim of this study was to estimate the prevalence of tobacco smoking among university students and to identify factors that may be related to both initiation and prevalence of tobacco smoking.…”
mentioning
confidence: 99%
“…MK & KM extracted data from the retrieved studies and discussed disagreements with the third coauthor (AN) as indicated. We used the structured sheets in Microsoft Excel® to extract the data including ( 1 ) authors, ( 2 ) publication year, ( 3 ) publication type, ( 4 ) site/s of study, ( 5 ) study implementation year, ( 6 ) type of study, ( 7 ) sampling method, ( 8 ) study population and sample size, ( 9 ) data gathering method, ( 10 ) language (Farsi, English), ( 11 ) Study scale (city, province, sub-national, national), ( 12 ) number of recruitment sites, ( 13 ) gender distribution, ( 14 ) age characteristics, ( 15 ) key socioeconomic indicators, ( 16 ) type of university, ( 17 ) major of university student, ( 18 ) prevalence of smoking.…”
Section: Methodsmentioning
confidence: 99%
“…Also the prevalence of cigarette smoking among Iranian youth was increasing 1). Various studies conducted in Iran reported the prevalence of cigarette smoking in college students from 9.8% to 18.48% ( 8 - 10 ). Thus, because there is no consensus about the recent prevalence rate of cigarette smoking in Iranian university students and because of notable increased in the prevalence rate of cigarette smoking among university student in Iran, we aimed to calculate the prevalence rate of cigarette smoking in college students by meta-analysis.…”
Section: Introductionmentioning
confidence: 99%